Repetir até ficar diferente: índices de uma experimentação acrobática e cênica com a Cia. Circo Lúdico Experimental - CE - Garcia, Samara do Nascimento (2017)
This research aims to reflect on the creative process of Cia. Experimental Circus - CLE in the composition of the show Quintal, starting in search of a contextualization of the work that we developed to think where it is inserted. To do so, he uses a genealogical perspective, also aesthetic and political, of circus language. The dramaturgical construction based on the investigation of an acrobatics for the scene and in a poetic outline given by the work of Manoel de Barros. Aiming to perceive the acrobatic technique in constant movement of construction and reconstruction in search of giving other senses to the risk and the virtuoso, founding elements of the circus aesthetics. Departing for reflections on the poetic tessituras that cross the creation, as well as on how we were raising during this process our methods, tools and resources. Based on the Critique of Processes, the study focuses on the observation, description and analysis of the scenic composition by proposing a reflection on the ways in which the creation and research in performing arts can be shared from a dynamic perspective of process documents.